The intersection of professionalism and interprofessional care: development and initial testing of the interprofessional professionalism assessment (IPA). Issue 1 (2nd January 2019) - Frost, Jody S.; Hammer, Dana P.; Nunez, Loretta M.; Adams, Jennifer L.; Chesluk, Benjamin; Grus, Catherine; Harvison, Neil; McGuinn, Kathy; Mortensen, Luke; Nishimoto, John H.; Palatta, Anthony; Richmond, Margaret; et al.
ABSTRACT: Valid assessment of interprofessional education and collaborative practice (IPECP) is challenging. The number of instruments that measure various aspects of IPECP, or in various sites is growing, however. The Interprofessional Professionalism Assessment (IPA) measures observable behaviors of health care professionals-in-training that demonstrate professionalism and collaboration when working with other health care providers in the context of people-centered care. The IPA instrument was created by the Interprofessional Professionalism Collaborative (IPC), a national group representing 12 entry-level health professions and one medical education assessment organization. The instrument was created and evaluated over several years through a comprehensive, multi-phasic process: 1) development of construct and observable behaviors, 2) instrument design, expert review and cognitive interviews, and 3) psychometric testing. The IPA contains 26 items representing six domains of professionalism (altruism and caring, excellence, ethics, respect, communication, accountability), and was tested by 233 preceptors rating health profession learners in the final year of their practical training. These preceptors represented 30 different academic institutions across the U.S., worked in various types of practice sites, and evaluated learners representing 10 different entry-level health professions. Exploratory factor analysis suggested four factors (communication, respect, excellence, altruism and caring) using 21 items with the least amount of missing data, and confirmed, for the most part, a priori expectations. Internal consistency reliability coefficients for the entire instrument and its four subscales were high (all greater than 0.9). Psychometric results demonstrate aspects of the IPA's reliability and validity and its use across multiple health professions and in various practice sites.